The Influence The Influence of Digital Marketing and Electronic Word of Mouth (E-Wom) With Brand Image Mediation on Purchase Decisions at Fore Surabaya - Muhammad Efendi Ibrahim; Liling Listyawati; Anita Asnawi; Galuh Ajeng Ayuningtiyas (International Journal of Management, Accounting & Finance (KBIJMAF), 2026)
This study is intended to investigate the impact of Digital Marketing and Electronic Word of Mouth (e-WOM) on Purchase Decisions, with Brand Image as a mediating variable in Fore Coffee consumers in Surabaya. This study applied a quantitative approach through causal methods, involving 100 respondents who had made transactions at Fore Coffee Sulawesi Street. The data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4 software. The findings of the study show that Digital Marketing and e-WOM have a positive and significant effect on Brand Image and Purchase Decisions. Brand image also has a significant influence on Purchase Decisions. In addition, Brand Image has proven to be a partial mediator, so Digital Marketing and e-WOM continue to have a direct influence, but the effect increases when through Brand Image. The research model produced an R² value of 0.671, which indicates good explanatory ability of the model. Overall, this study emphasizes that strengthening digital marketing strategies, managing e-WOM, and building a consistent brand image is very important in improving consumer purchasing decisions of Fore Coffee.